ANTIMICROBIAL AND ANTIOXIDANT ACTIVITIES OF EXTRACTS OF Euphorbia rigida Bieb - Metin M.; Bürün B. (Journal of Animal and Plant Sciences, 2023)
The aim of this study was to determine antioxidant and antimicrobial activities of extracts of the Euphorbia rigida (Bieb.) plant which was extracted by using water, acetone, methanol, hexane and chloroform solution. Antimicrobial activity was determined by disc diffusion method against Pseudomonas aeruginosa,Staphylococcus aureus and Candida albicans. Antioxidant activity was determined by using β-carotene-linolenic acid, DPPH method, metal chelating activity, Cuprac and by evaluating the content of total phenolic compounds. Total antioxidant activities of E. rigida plant extracts at 50 and 100 μg/ml concentrations were compared against standard antioxidant activities such as BHT, α-tocopherol and quercetin activity. All extracts from E. rigida, except the chloroformic extract, showed antimicrobial activity against P. aeruginosa. However no activity was found against S. aureus and C. albicans. Antioxidant activities were found to be close to those of synthetic antioxidants such as BHT and α-tocopherol. The results indicate that E. rigida plant extracts can be used as a new and alternative antimicrobial agent against P. aeruginosa. It can also be argued that acetone and hexane extracts of E. rigida have the potential of becoming a natural antioxidant source. Moreover, all extracts from E. rigida might have important industrial, biotechnological, medical, agricultural, ecologial and economic potential.
Keywords: Antimicrobial activity; antioxidant activity; Euphorbia rigida; plant extracts